A Narrative and Critical Review of Randomized-Controlled Clinical Trials on Patent Foramen Ovale Closure for Reducing the Risk of Stroke Recurrence - Safouris, Apostolos; Kargiotis, Odysseas; Psychogios, Klearchos; Kalyvas, Pericles; Ikonomidis, Ignatios; Drakopoulou, Maria; Toutouzas, Konstantinos; Tsivgoulis, Georgios (Frontiers in Neurology, 2020)
Patent foramen ovale (PFO) is a common cardiac anatomic variant that has been increasingly found in young (<60 years) cryptogenic stroke patients. Despite initial neutral randomized-controlled clinical trials (RCTs), there have been four recent RCTs providing consistent data in favor of the efficacy and safety of PFO closure compared to medical therapy for secondary stroke prevention. However, taking into consideration the high prevalence of PFO, the low risk of stroke recurrence under medical treatment and the uncommon yet severe adverse events of the intervention, patient selection is crucial for attaining meaningful clinical benefits. Thorough workup to exclude alternative causes of stroke and identification of high-risk PFOs through clinical, neuroimaging and echocardiographic criteria are essential. Cost effectiveness of the procedure cannot be proven for the time being, since there are no robust data on clinical outcome after PFO-associated stroke but only limited anecdotal data suggesting low risk for long-term disability.